wasail ta'lim lugah al-arabiyah: fahm wa fawaid wa maayiir al-ikhtibaar - nimah, khoirin; isnawati, zakiyah (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
AbstractToday, the field of learning, in general, is influenced by advancements and discoveries in the fields of skills, science, and technology. This influence is evident in the efforts to renew the education and learning system, with one of the means of renewal being learning media. In this article, the author invites the reader to discuss various issues related to Arabic language learning media, including understanding learning media, the functions and benefits of learning media, criteria for selecting learning media, different types of Arabic language learning media, and how these media contribute to the enhancement of education in the modern era. Keywords: Educational media, teaching skills, educational technology. ???? ??????????? ????? ???? ?????? ???? ??? ????????? ??????????? ?? ?????? ???????? ??????? ????????????. ???? ??? ??????? ?? ?????? ???????? ?????? ???? ??????? ???????? ??? ????? ????? ?????? ????? ?? ????? ???????. ?? ??? ??????? ???? ?????? ?????? ??????? ????? ?????? ??? ??? ?????? ???? ????? ???????? ??? ?? ??? ??? ????? ??????? ???????? ????????? ??????? ????????? ???????? ????????? ?????? ????? ??? ??????? ?? ????? ??????? ?? ????? ??????..??????? ?????????: ????? ???????? ?????? ???????? ????????? ???????.